Production of Cellulase Enzyme from Aspergilus niger using Rice Husk and Bagasse as Inducer - Purkan Purkan; HD Purnama; S Sumarsih (Jurnal ILMU DASAR, 2015)
Aspergillus niger is fungi can produce cellulase enzyme with agriculture waste as natural inducers. The purpose of this study was to compare the natural inducers potential between rice husk and bagasse to produce cellulase enzyme from Aspergillus niger. Production of cellulase enzyme was done with variety of inducers such as CMC, rice husk, and bagasse. The optimization of enzyme production includes optimum production time, inducer type, and optimum concentration of inducer. Furthermore, the enzyme also was characterized in pH and temperature. Enzyme activity test using the DNS method with CMC as substrate. According of this test result show that highest cellulase enzyme activity has production time for 108 hours with rice husk as inducer. The optimum rice husk concentration was needed of 2.5%. The cellulase enzyme was induced by rice husk has optimum activity at pH 4 and 50°C of 0.709 IU/mL.   Keywords : cellulase enzymes, Aspergillus niger, inducers, rice husk, bagasse.